A Novel Invadopodia-Specific Marker for Invasive and Pro-Metastatic Cancer Stem Cells - Huang, Shenq-Shyang; Liao, Wen-Ying; Hsu, Chung-Chi; Chan, Tze-Sian; Liao, Tai-Yan; Yang, Pei-Ming; Chen, Li-Tzong; Sung, Shian-Ying; Tsai, Kelvin K. (Frontiers in Oncology, 2021)
Introduction: Stem-like cancer cells or cancer stem cells (CSCs) may comprise a phenotypically and functionally heterogeneous subset of cells, whereas the molecular markers reflecting this CSC hierarchy remain elusive. The glycolytic enzyme alpha-enolase (ENO1) present on the surface of malignant tumor cells has been identified as a metastasis-promoting factor through its function of activating plasminogen. The expression pattern of surface ENO1 (sENO1) concerning cell-to-cell or CSC heterogeneity and its functional roles await further investigation. Methods: The cell-to-cell expression heterogeneity of sENO1 was profiled in malignant cells from different types of cancers using flow cytometry. The subcellular localization of sENO1 and its functional roles in the invadopodia formation and cancer cell invasiveness were investigated using a series of imaging, molecular, and in vitro and in vivo functional studies. Results: We showed here that ENO1 is specifically localized to the invadopodial surface of a significant subset (11.1%-63.9%) of CSCs in human gastric and prostate adenocarcinomas. sENO1+ CSCs have stronger mesenchymal properties than their sENO1- counterparts. The subsequent functional studies confirmed the remarkable pro-invasive and pro-metastatic capacities of sENO1+ CSCs. Mechanistically, inhibiting the surface localization of ENO1 by downregulating caveolin-1 expression compromised invadopodia biogenesis, proteolysis, and CSC invasiveness. Conclusions: Our study identified the specific expression of ENO1 on the invadopodial surface of a subset of highly invasive and pro-metastatic CSCs. sENO1 may provide a diagnostically and/or therapeutically exploitable target to improve the outcome of patients with aggressive and metastatic cancers.